Assess the Effect of Detract Technique among Post-operative Toddlers with Cleft Lip and Cleft Palate - Linda Xavier; Sowndariya Velmurugan (Wolters Kluwer Medknow Publications, 2024)
Background: Children who undergo surgery frequently experience postoperative pain or POP. Pain experienced by children can be addressed as a basic human right. Because hospitals can be extremely stressful places for families and their children, pain, and discomfort associated with intrusive techniques can lengthen hospital stays for children and lead them to heal more slowly than they would have otherwise. Engaging the kids in intellectual pursuits is one way to use distraction techniques to take their minds off unpleasant stimuli and lessen their suffering. Purpose: The current study's goal was to evaluate the impact of the distract technique on postoperative infants with cleft lip and palate who were between the ages of 1 and 3 years old. Materials and Methods: The Saveetha Medical College and Hospital served as the host institution for the quantitative method with a preexperimental investigation. Sampling Method: Convenience sampling was used to select 60 postoperative children with cleft lip and palate who were between the ages of one and three. Interventions: One intervention group and a control group were randomly assigned to each of the 60 postoperative youngsters. Distract technique (tactile ball) was started for the intervention group 20 min prior to operation day and continued for 30 days. The first group (the control group) received standard care, which included analgesic medication. The second group (the intervention group) received no analgesic medication and was played with a tactile ball by a nurse who happened to be one of the researchers working in the pediatric unit where the study was conducted. Acetaminophen (10-15 mg/kg) was given to the children in the control group as an analgesic. Results: The descriptive analysis (P > 0.05) did not reveal any statistically significant differences between the groups.